Investigação e análise de anomalias de código em aplicações Web - Luna, Sérgio Giordanno Medeiros de (2021)
Web applications represent a significant part of today's computer systems. As in any other software system, their implementation may be affected by poor programming practices and violations of fundamental principles in Software Engineering. These problems are known as code anomalies (also known as code smells or bad smells), which refer to an apparent symptom of a more severe problem in the source code. While not preventing the system from working correctly, code anomalies can hamper development and generate future risks, especially with regards to understanding and maintenance. Although the literature presents many studies on code anomalies in traditional software systems, a few studies analyze such anomalies specifically in Web applications and how to detect them. There are also not many studies aiming to verify if the anomalies that occur in traditional software systems, already widely studied, are observed in Web applications or if there are anomalies specific to this context. Furthermore, the literature does not still present an overview of the state of the art regarding the investigation of code anomalies in Web applications. Aiming to fill this gap, this work investigates code anomalies in Web applications and identifies how they occur and can be detected. For this purpose, a systematic mapping study was carried out. Primary studies available in the literature were collected and analyzed through well-defined procedures and criteria and following consolidated guidelines. This work presents the main results of the performed systematic mapping study, providing (i) an overview of the occurrence of code anomalies in the context of Web applications, their frequency, and where they are observed, (ii) an identification of the approaches and tools used to detect them, and (iii) if and how aspects of refactoring are considered in this context.